2006
DOI: 10.1002/app.23749
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet grafting of styrene and maleic anhydride on polyethylene‐terephthalate film

Abstract: UV-induced graft copolymerization with mixed monomers such as styrene (St) and maleic anhydride (MAH) onto the surface of polyethylene-terephthalate (PET) films was carried out. The chemical properties and the morphology of the surface of grafted films were investigated via attenuated total reflection (ATR) , scanning electron microscopy (SEM), and atomic force microscopy (AFM) techniques. ATR images revealed that MAH was succeeded in being grafted. On the other hand, SEM and AFM analysis showed that many gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…It has been reported that maleic anhydride can be grafted to low density poly(ethylene) (LDPE) after UV irradiation without a photoinitiator 8. Other monomer chemistries that have also been shown to be able to be UV surface grafted to materials such as LDPE and poly(ethylene terephthalate) without a phototinitiator include styrene, acrylic acid, methacrylic acid, glycidyl methacrylate, and 2‐hydroxyethly acrylate 1, 9, 10, 19, 35, 36. There are also limited reports on the direct polymerization of vinyl monomers from pp films 4–6.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that maleic anhydride can be grafted to low density poly(ethylene) (LDPE) after UV irradiation without a photoinitiator 8. Other monomer chemistries that have also been shown to be able to be UV surface grafted to materials such as LDPE and poly(ethylene terephthalate) without a phototinitiator include styrene, acrylic acid, methacrylic acid, glycidyl methacrylate, and 2‐hydroxyethly acrylate 1, 9, 10, 19, 35, 36. There are also limited reports on the direct polymerization of vinyl monomers from pp films 4–6.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the preparation of mixed layers in order to enrich the surface chemistry has received less attention. As an example, mixed monomers providing charge transfer complexes such as styrene and vinyl acetate or maleic anhydride have been photografted to improve the surface properties of PET. , Two incompatible enzymes (trypsin and transglutaminase) were separately encapsulated into different poly­(ethylene glycol) (PEG) network layers and grafted on a polyethylene film via visible-light-induced living photografting polymerization . Electrografting also allows the preparation of mixed layers.…”
Section: Introductionmentioning
confidence: 99%
“…UtvrĎeno je da su membrane ovog kopolimera bolje od čistog PET-a kada je u pitanju razdvajanje smeša tečnosti parcijalnim isparavanjem (pervaporacija), u ovom slučaju toluen/metanol sistema [47,48]. Dobijanje kalemljenih kopolimera PS i PET moţe se indukovati i UV zračenjem, uz korišćenje ţivinih lampi, snage 1000 W, pri čemu je talasna duţina zračenja iznosila 365 nm, a rastojanje izmeĎu uzoraka i izvora zračenja 10 cm [49]. Kalemljeni polimeri PS mogu se koristiti i u medicini.…”
Section: Kalemljeni Kopolimeri Polistirena I Sintetskih Polimeraunclassified